Learning Disabilities : Themes and perspectives (Oxford : Butterworth-Heinemann, 2002)
This text presents vignettes based on real cases which relate chapter themes to clinical practice, and discusses issues, opening new avenues to enhanced care in difficult circumstances.
Keywords: Learing disabled -- Medical care; Physical nursing; Health and Fitness